Carotenoid-Enriched Fractions From Spondias mombin Demonstrate HER2 ATP Kinase Domain Inhibition: Computational and In Vivo Animal Model of Breast Carcinoma Studies - Metibemu, Damilohun Samuel; Akinloye, Oluseyi Adeboye; Omotuyi, Idowu Olaposi; Okoye, Jude Ogechukwu; Popoola, Mustapha Ayodele; Akamo, Adio Jamiu (Frontiers in Oncology, 2021)
Human epidermal growth factor 2 (HER2) is overexpressed in about 20% of breast cancer and is associated with a poor prognosis. We report in this study that carotenoid-enriched fractions from Spondias mombin demonstrate HER2 ATP kinase domain inhibition. HER2 breast carcinoma was modeled in female Wistar rats and authenticated via immunohistochemical studies. Inhibition of HER2 ATP kinase domain by the carotenoid-enriched fractions was investigated by molecular docking, atomistic simulation, and the expression of HER2 mRNA in HER2 positive breast carcinoma model in female Wistar rats. The therapeutic efficacy of the treatments (carotenoid-rich fractions) was determined by biochemical, tumor volume, and histopathological analysis. Immunohistochemical analysis revealed DMBA-induced HER2-positive breast carcinoma. Phytoconstituents of the carotenoid-enriched fractions; astaxanthin, 7,7',8,8'-tetrahydro-β,β-carotene, beta-carotene-15,15'-epoxide, and lapatinib (standard drug) demonstrate inhibition of HER2 with docking scores of -3.0 kcal/mol, -8.5 kcal/mol, -11.5 kcal/mol, and -10.6 kcal/mol respectively and during atomistic simulation, the compounds ruptured the canonical active-state K753/E770 salt-bridge interaction. The treatment similarly downregulated HER2 mRNA expression significantly at p <0.05. It also upregulated the expression of p53 and p27 mRNAs significantly at p <0.05 and reduced creatinine and urea concentrations in the serum at p <0.05. The tumor volume was also significantly reduced when compared with the untreated group. Carotenoid-enriched fractions from Spondias mombin demonstrate anti-HER2 positive breast carcinoma potentials via HER2 ATP kinase domain inhibition.